2001
DOI: 10.1128/mcb.21.14.4626-4635.2001
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CIITA Function by Protein Kinase A (PKA)-Mediated Phosphorylation: Mechanism of Prostaglandin E, Cyclic AMP, and PKA Inhibition of Class II Major Histocompatibility Complex Expression in Monocytic Lines

Abstract: Prostaglandins, pleiotropic immune modulators that induce protein kinase A (PKA), inhibit gamma interferon induction of class II major histocompatibility complex (MHC) genes. We show that phosphorylation of CIITA by PKA accounts for this inhibition. Treatment with prostaglandin E or 8-bromo-cyclic AMP or transfection with PKA inhibits the activity of CIITA in both mouse and human monocytic cell lines. This inhibition is independent of other transcription factors for the class II MHC promoter. These same treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 64 publications
2
45
0
Order By: Relevance
“…CIITA transcription is highly regulated (6,(31)(32)(33)(34), and posttranslational mechanisms also affect CIITA activity (35,36). Transcriptional regulation of CIITA occurs through the actions of three independent promoters (pI, pIII, pIV) in mice.…”
Section: Ciita Controls the Expression Of Mhc-ii By All Types Of Apcsmentioning
confidence: 99%
“…CIITA transcription is highly regulated (6,(31)(32)(33)(34), and posttranslational mechanisms also affect CIITA activity (35,36). Transcriptional regulation of CIITA occurs through the actions of three independent promoters (pI, pIII, pIV) in mice.…”
Section: Ciita Controls the Expression Of Mhc-ii By All Types Of Apcsmentioning
confidence: 99%
“…An important facet of the present study is that the X2 box, now securely identified as the cAMP response element (CRE) octamer (15), receives signals from G protein-coupled seven-pass receptors (16) that bind modulators of MHC II expression. Well-characterized examples of such modulators include thyroid-stimulating hormone (17) and prostaglandin E2 (18), although in the latter case signaling via CIITA is also involved. The octamer varies, particularly in its 3Ј tetramer (19), and a major human disease-associated polymorphism occurs 10 bp upstream of CRE in the IL-6 promoter (20).…”
mentioning
confidence: 99%
“…Thus, the instability of CIITA mRNA or protein has been recently hypothesized to explain the defect in CIITA protein and the consequent lack of MHC-II expression in a murine tumor cell line (Naves et al, 2002). In addition, other observations indicate that post-translational modifications, such as phosphorylation (Li et al, 2001;Tosi et al, 2002) or acetylation (Spilianakis et al, 2000) play an important role in CIITA stability or nuclear shuttling. Our data indicate that SK-NB-E2(c) transfected with CIITA gene express low levels of cytoplasmic CIITA protein, suggesting that a reduced CIITA protein accumulation or a deficient CIITA Figure 7 Analysis of CIITA nuclear localization by confocal microscopy.…”
Section: Discussionmentioning
confidence: 98%